Pembuktian Validitas terkait Struktur Tes Potensi Akademik Pascasarjana (PAPS) Universitas Gadjah Mada - Wahyu Widhiarso (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study examined the construct validity of the Graduate Academic Potential Test (PAPS). The examination was performed on all existing PAPS series (6 forms) to identify the consistency of dimensionality structure of PAPS. Data of this study were analyzed using confirmatory factor analysis (CFA). The results of the analysis support assumption that the structure of the PAPS test is unidimensional. All of the model fit indices support the decision that the unidimensional model fit the data. The study also examined factor loading that the non-verbal components, especially the quantitative components that had a higher factor weight than the other components.